Reduced Graphene Oxide/Maghemite Nanocomposite for Detection of Hydrocarbon Vapor Using Surface Plasmon Resonance - Alwahib, A.A.; Sadrolhosseini, A.R.; An'amt, M.N.; Lim, H.N.; Yaacob, M.H.; Abu Bakar, M.H.; Ming, H.N.; Mahdi, M.A. (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In this paper, a reduced graphene oxide/maghemite (rGO/γ-Fe2O3) nanocomposite film was used as the sensing layer using surface plasmon resonance (SPR) technique. The fabricated SPR sensor was based on a trilayer structure in which the rGO/γ-Fe2O3 nanocomposite layer was sandwiched between two gold layers. The SPR sensor was tested with hydrocarbon materials such as acetone, ethanol, methanol, and propanol. Based on the findings, the resonance angle shift with the presence of acetone is 1.891°, the largest among other hydrocarbon materials. The sensitivity of resonance angle shift toward acetone concentration is 0.0368°/%. These results demonstrate the massive potential of rGO/γ-Fe2O3 nanocomposite material for optical sensing applications.